2005
DOI: 10.1074/jbc.m503366200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Inositol Hexakisphosphate (InsP6) Protect HEK293 Cells from Tumor Necrosis Factor α- and Fas-induced Apoptosis

Abstract: The overexpression of inositol 1,3,4-trisphosphate 5/6-kinase has recently been shown to protect HEK293 cells from tumor necrosis factor ␣ (TNF␣)-induced apoptosis. This overexpression leads to an increase in the levels of both inositol 1,3,4,5,6-pentakisphosphate (InsP 5 ) and inositol 1,2,3,4,5,6-hexakisphosphate (InsP 6 ). Cells that overexpress InsP 5 2-kinase have increased levels of InsP 6 and are also protected from TNF␣-induced apoptosis; furthermore, cells that express an RNA interference construct to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Previous work in mammalian cells demonstrated that IP 6 is protective from apoptosis (41), consistent with our results that loss of IP production leads to increased cell death.…”
supporting
confidence: 82%
“…Previous work in mammalian cells demonstrated that IP 6 is protective from apoptosis (41), consistent with our results that loss of IP production leads to increased cell death.…”
supporting
confidence: 82%
“…An interaction protein of IP6K2, TRAF2 (Morrison et al , 2007 ) also participates in this anti-apoptotic signaling of TNF receptors. Furthermore, Verbsky and Majerus (2005) showed that increased levels of InsP 6 due to its forced biosynthesis protect HEK293 cells from apoptosis derived by TNF-α and they speculated whether pyrophosphorylated inositols might be responsible for the protection (Verbsky and Majerus , 2005 ). These data together might indicate a linkage between TNF-α signaling protein components, DPIPs, and their respective kinases.…”
Section: Future Researchmentioning
confidence: 93%
“…Both the protein kinase Irak2 and adaptor protein Myd88 play key roles in the activation of NFκB [22], whereas Traf3 has been shown to inhibit NFκB activation [23]. The role of the enzyme Ippk is still unclear, but it has been shown to play a role in the inhibition of apoptosis [24]. In addition, c-jun is also up-regulated in comparison to the ISO stimulated nuclei.…”
Section: Targets Of β-Adrenergic Transcriptional Responses In Isolatementioning
confidence: 99%